Beef quality with different intramuscular fat content and proteomic analysis using isobaric tag for relative and absolute quantitation of differentially expressed proteins. (August 2016) - Mao, Yanwei; Hopkins, David L.; Zhang, Yimin; Li, Peng; Zhu, Lixian; Dong, Pengcheng; Liang, Rongrong; Dai, Jin; Wang, Xiaoyun; Luo, Xin
Abstract: Intramuscular fat (IMF) is an important trait for beef eating quality. The mechanism of how IMF is deposited in beef cattle muscle is not clear at the molecular level. The muscle ( M. longissimus lumborum : LL) of a group of Xiangxi yellow × Angus cattle with high fat levels (HF), was compared to the muscle of a low fat group (LF). The meat quality and the expressed protein patterns were compared. It was shown that LL from the HF animals had a greater fat content (P < 0.05) and lower moisture content (P < 0.05) than LL from LF animals. Forty seven sarcoplasmic proteins were differentially expressed and identified between the two groups. These proteins are involved in 6 molecular functions and 16 biological processes, and affect the Mitogen-activated protein kinases pathway, insulin pathway and c-Jun N-terminal kinases leading to greater IMF deposition. Cattle in the HF group had greater oxidative capacity and lower glycolytic levels suggesting a greater energetic efficiency.